Rezolvati in Z ecuatia:
(x+3)(x-2)=0
Răspunsuri la întrebare
Răspuns de
1
(x+3)(x-2)=0⇒(x²-2x+3x-6=0⇒x²+x-6=0
a=1
b=1
c=-6
Δ=b²-4ac⇒Δ=(1)²-4×1×(-6)⇒Δ=1+24⇒Δ=25⇒√Δ=√25⇒Δ=5
x1x2=-b+-√Δ/2a⇒
x1=-1+5/2⇒4/2⇒x1=2
x2=-1-5/2⇒-6/2⇒x2=-3
sucees
a=1
b=1
c=-6
Δ=b²-4ac⇒Δ=(1)²-4×1×(-6)⇒Δ=1+24⇒Δ=25⇒√Δ=√25⇒Δ=5
x1x2=-b+-√Δ/2a⇒
x1=-1+5/2⇒4/2⇒x1=2
x2=-1-5/2⇒-6/2⇒x2=-3
sucees
Alte întrebări interesante
Matematică,
8 ani în urmă
Engleza,
8 ani în urmă
Matematică,
9 ani în urmă
Limba română,
9 ani în urmă
Matematică,
9 ani în urmă
Limba română,
9 ani în urmă